2020
DOI: 10.3390/ijms21114007
|View full text |Cite
|
Sign up to set email alerts
|

From the Argonauts Mythological Sailors to the Argonautes RNA-Silencing Navigators: Their Emerging Roles in Human-Cell Pathologies

Abstract: Regulation of gene expression has emerged as a fundamental element of transcript homeostasis. Key effectors in this process are the Argonautes (AGOs), highly specialized RNA-binding proteins (RBPs) that form complexes, such as the RNA-Induced Silencing Complex (RISC). AGOs dictate post-transcriptional gene-silencing by directly loading small RNAs and repressing their mRNA targets through small RNA-sequence complementarity. The four human highly-conserved family-members (AGO1, AGO2, AGO3, and AGO4) demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 257 publications
(272 reference statements)
0
6
0
Order By: Relevance
“…Past relevant analyses have emphasized on miRNA loading and the distinction between the bound and unbound states of AGO2, as the structures of AGO3 and AGO4 became recently available. Genomic studies have solidified the distinction of the AGOs in expression under different conditions or tissues, affecting the biological operations of the organism or causing disease 7 . To complement previous findings, we performed molecular dynamics simulations of each AGO unbound state to acquire an insight on their mechanistic details.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Past relevant analyses have emphasized on miRNA loading and the distinction between the bound and unbound states of AGO2, as the structures of AGO3 and AGO4 became recently available. Genomic studies have solidified the distinction of the AGOs in expression under different conditions or tissues, affecting the biological operations of the organism or causing disease 7 . To complement previous findings, we performed molecular dynamics simulations of each AGO unbound state to acquire an insight on their mechanistic details.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of four members in the human AGO protein family should be explored under a biochemical perspective, extending the existing relevant knowledge from genomics. AGO proteins and their guides have been reported that exhibit a varying profile in expression within the human tissues 7,87,88 . However, each human tissue has its own range of pH values that facilitates the normal operation of the associated biological processes such as membrane transport and normal cellular division.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the present stage of research, it is difficult to determine the role of angiogenin nuclease in cutting the anticodon loop. Angiogenin cleaves C–A and U–A sequences [ 49 , 50 ]. In the analyzed tRNAs, the C–A base pair occurs twice, in tRNAGly(CCC) and tRNAVal(AAC), and in both cases it is cleaved.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, it was shown that the 23 nt long variant svRNAb was derived from vtRNA1-1 and that Dicer, a component of the miRNA pathway, was involved in the processing. The authors also demonstrated that svRNAb, similar to miRNAs, could both guide sequence-specific cleavage of a complementary target RNA in vitro and bind to some Argonaute proteins, the core components of the RNA-induced silencing complex (RISC) [ 108 ]. Based on these findings, it was proposed that svRNAb shares mechanisms of gene expression regulation with miRNA.…”
Section: The Involvement Of the Vault Nanoparticle In Normal And Pmentioning
confidence: 99%